2013
DOI: 10.1017/s1368980013001924
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality in young adults and its association with food-related behaviours

Abstract: Objective: To determine the diet quality of a group of young adults and explore its associations with two food-related behaviours (involvement in meal preparation and consumption of commercially prepared meals). Design: Cross-sectional study of young adults. Sample characteristics, food-related behaviours and dietary intake were assessed using a self-administered questionnaire including an FFQ. Diet quality was measured using the fifteen-item Dietary Guideline Index (DGI) designed to assess adherence to Austra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 47 publications
2
78
2
3
Order By: Relevance
“…One possible explanation may be related to how people define the term "cooking"-it may have different meanings, ranging from cooking from raw ingredients to microwaving ready-to serve foods. This supports the notion that public nutrition messages should explicitly endorse cooking more meals at home to address the heterogeneity of what it means to cook for Canadian university students (Thorpe, Kestin, Riddell, Keast, & McNaughton, 2014;Wolfson, Bleich, Smith, & Frattaroli, 2016 Not surprisingly, among our respondents, 42% (n = 362) report having an overloaded schedule and that, as a result, they look for food they can quickly buy, make and swallow. This is in line with the expected results.…”
Section: The Planet-nutrition-kitchen Loversupporting
confidence: 78%
“…One possible explanation may be related to how people define the term "cooking"-it may have different meanings, ranging from cooking from raw ingredients to microwaving ready-to serve foods. This supports the notion that public nutrition messages should explicitly endorse cooking more meals at home to address the heterogeneity of what it means to cook for Canadian university students (Thorpe, Kestin, Riddell, Keast, & McNaughton, 2014;Wolfson, Bleich, Smith, & Frattaroli, 2016 Not surprisingly, among our respondents, 42% (n = 362) report having an overloaded schedule and that, as a result, they look for food they can quickly buy, make and swallow. This is in line with the expected results.…”
Section: The Planet-nutrition-kitchen Loversupporting
confidence: 78%
“…The overall less favorable diet quality of younger respondents has been consistently found in other research [33,34,35,36], and it has been suggested that age is one of the most important modifiers of diet quality [37]. Younger populations have been shown to be more likely to consume commercially prepared meals (takeaways and eating out), which displace healthier foods in the diet [38]. Australian young adults have been shown to be a group at high risk of weight gain over the past few decades [39,40].…”
Section: Discussionmentioning
confidence: 71%
“…Participants who prioritized preparing food from whole ingredients coped with time constraints by making large batches of soups or stews to facilitate leftovers. Existing studies indicate that increased diet quality is associated with greater frequency of cooking and using more complex preparation steps (Larson et al, 2006;Thorpe, Kestin, Riddell, Keast, & McNaughton, 2013). Therefore, this study suggests that creating food learning opportunities prior to transitioning to independent living could potentially pique interest in cooking, which was associated with a variety of healthy food behaviours.…”
Section: Discussionmentioning
confidence: 82%